Balanced scorecard as a strategic alignment tool for employees - Ferreira, Miguel Casas Rocha (2022)
The thesis in question tries to understand how the use of a strategic management tool, more specifically the Balance Scorecard, allows aligning the company's strategic objectives with the company's employees. Given the importance that the worker has received over the years, it is important to understand how their integration can be essential. It is necessary to understand if there is any type of action on the achievement of stipulated objectives, whether financial or non-financial incentives, on the fulfillment of the same. We chose to adopt a qualitative methodological perspective, using the case study, where, through an interview conducted with a member of the board of directors of Corticeira Amorim and an employee, it was possible to clarify certain aspects on the research question, taking into account as well the sustainability report and the consolidated accounts from the company. During the interview, it was possible to understand how the tool was implemented in the company and in the respective operations in order to understand if there is, at an initial stage, a correct application of the tool; understand how the company managed to form the alignment between the strategic objectives and its employees; and finally, verifying whether all workers are rewarded for meeting established goals. The results indicate that the company is able to effectively carry out its integration of objectives with employees, but the incentives linked to the company's strategic objectives are not connected with all employees. Only managers get a “direct” reward on the objectives set by the Balanced Scorecard tool.